Neonatal microbiota-epithelial interactions that impact infection - Negi, Shikha; Hashimoto-Hill, Seika; Alenghat, Theresa (Frontiers in Microbiology, 2022)
Despite modern therapeutic developments and prophylactic use of antibiotics during birth or in the first few months of life, enteric infections continue to be a major cause of neonatal mortality and morbidity globally. The neonatal period is characterized by initial intestinal colonization with microbiota and concurrent immune system development. It is also a sensitive window during which perturbations to the environment or host can significantly impact colonization by commensal microbes. Extensive research has demonstrated that these early life alterations to the microbiota can lead to enhanced susceptibility to enteric infections and increased systemic dissemination in newborns. Various contributing factors continue to pose challenges in prevention and control of neonatal enteric infections. These include alterations in the gut microbiota composition, impaired immune response, and effects of maternal factors. In addition, there remains limited understanding for how commensal microbes impact host-pathogen interactions in newborns. In this review, we discuss the recent recognition of initial microbiota-epithelial interactions that occur in neonates and can regulate susceptibility to intestinal infection. These studies suggest the development of neonatal prophylactic or therapeutic regimens that include boosting epithelial defense through microbiota-directed interventions.